Evaluation of the Biological Activity of Three Green Algae Collected from Hon Son Island, Kien Giang Province, Viet Nam: Biological Activity of Three Green Algae Collected from Hon Son Island - Men, Tran Thanh; Nhu, Huynh; Thao, Truong Thi Phuong; Nga, Pham Thi Ngoc; Quy, Tran Ngoc (Journal of Tropical Life Science, 2026)
Chaetomorpha spiralis, Caulerpa microphysa, and Caulerpa sp., which belong to the Chlorophyta group (commonly known as green algae), are increasingly recognized as rich sources of natural substances with biological activities. These marine resources are of particular interest among green algae due to their potential to yield novel, safe, and effective compounds. This study, therefore, aimed to demonstrate the specific bioactive value of crude solvent extracts from the above algae species by systematically evaluating their antioxidant and UV protection activities, which are critical properties for dermatological and pharmaceutical applications. The measurement of antioxidant effect was performed by two well-established assay methods: DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging and ABTS•+ (2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid), along with in vitro spectrophotometric (SPF) analysis to determine the sun protection factor. After analysis, the Caulerpa sp. sample exhibited the highest DPPH radical scavenging activity, with an IC50 value of 18.54%. At the same time, Chaetomorpha spiralis showed the most excellent ABTS•+ radical neutralizing activity, with 12.89% of the IC50 value. The Chlorophyta extract exhibited relatively low antioxidant activity, with IC50 values exceeding 4.0 mg/mL in both assays. The SPF value of the Caulerpa sp. extract was the highest among the species tested, reaching 41.50 mg/mL (a significant finding for photoprotection). These findings collectively highlight the potential of Chlorophyta extracts. Despite variable antioxidant results, their utility in antioxidant, antibacterial, and skincare applications, particularly in cosmeceuticals, warrants further investigation.